OPTIMASI KONSENTRASI LARUTAN KAPUR SIRIH UNTUK MENETRALKAN ASAM LEMAK BEBAS (ALB) PADA MINYAK GORENG - Sinaba, Berry; Tani, Djefri; Tuerah, Jeanne (Chemistry Department, Universitas Negeri Manado, 2025)
Oil is a triglyceride compound that is liquid at room temperature. Oil can experience changes in aroma and taste during storage. To overcome the damage to the oil, neutralization is carried out. Neutralization is a process to break free fatty acids from oil or fat, by reacting free fatty acids with bases or other reagents, thus forming soap (soap stock) with the aim of purifying oil, reducing residual gum, improving taste, and reducing darkness from the oil. Neutralization can be done in various ways, namely by using alkali, sodium carbonate, ammonia, or by using steam. This study aims to determine the optimum concentration of whiting solution in neutralizing free fatty acids. Neutralization was carried out with several concentrations, namely 10%, 12%, 14%, 16%, 18%, 20%. The test parameters in this study were free fatty acid content, acid number, peroxide value and water content. Based on the results obtained the optimum concentration was 16% with free fatty acids 0.1781, acid number 0.25, peroxide number 4.39, water content 0.39.